The Use of Recollection Rejection in the Misinformation Paradigm. Issue 6 (November 2016) - Moore, Kara N.; Lampinen, James Michael
Summary: The purpose of this research was to determine the role of recollection rejection in the rejection of misinformation. In Experiment 1, we examined the use of recollection rejection to reject contradictory and additive misinformation. We measured recollection rejection by comparing misinformation acceptance rates, graphing confidence‐accuracy data using phantom receiver operating characteristic curves, examining high confidence rejections of misinformation, and examining self‐report responses. These measures converged on the finding that participants used recollection rejection to reject both types of misinformation but used recollection rejection more on contradictory misinformation. In Experiment 2, we manipulated the delay between the event and misinformation and between misinformation and test. The length of both of these delays affected misinformation acceptance. Participants were more likely to use recollection rejection to reject contradictory misinformation after a short delay before encountering misinformation. Overall these findings indicate that people can spontaneously induce recollection rejection to reject misinformation and prevent false memories. Copyright © 2016 John Wiley & Sons, Ltd.